Interactions between Hsp70 and the Hydrophobic Core of α-Synuclein Inhibit Fibril Assembly - Luk, Kelvin C; Mills, Ian P; Trojanowski, John Q; Lee, Virginia M.-Y (Biochemistry (Easton), 2008)
Molecular chaperones of the heat shock protein 70 (Hsp70) family counteract protein misfolding in a variety of neurodegenerative disease models. To determine whether human Hsp70 exerts similar effects on the aggregation of α-synuclein (α-Syn), the key component of insoluble fibrils present in Parkinson’s disease, we investigated α-Syn fibril assembly in the presence of Hsp70. We found in vitro assembly was efficiently inhibited by substoichiometric concentrations of purified Hsp70 in the absence of cofactors. Experiments using α-Syn deletion mutants indicated that interactions between the Hsp70 substrate binding domain and the α-Syn core hydrophobic region underlie assembly inhibition. This assembly process was inhibited prior to the elongation stage as we failed to detect any fibrils by electron microscopy. In addition, fluorescence polarization and binding assays suggest that Hsp70 recognizes soluble α-Syn species in a highly dynamic and reversible manner. Together, these results provide novel insights into how Hsp70 suppresses α-Syn aggregation. Furthermore, our findings suggest that this critical step in Parkinson’s disease pathogenesis may be subject to modulation by a common molecular chaperone.